Kunst der 60er und 70er Jahre aus Bonner Privatbesitz. - Kunstmuseum Bonn (Bonn : Kunstmuseum Bonn, 1976)
Schumacher, Emil ; Schreiter, Johannes ; Brüning, Peter ; Ursula ; Hrdlicka, Alfred ; Schultze, Bernard ; Antes, Horst ; Iseli, Rolf ; Bödeker, Erich ; Lichtenstein, Roy ; Klein, Yves ; Arman ; Spoerri, Daniel ; Lohse, Richard Paul ; Mack, Heinz ; Piene, Otto ; Luther, Adolf ; Uecker, Günther ; Aubertin, Bernard ; Twombly, Cy ; Girke, Raimund ; Graubner, Gotthard ; Jochims, Raimer ; Bonato, Victor ; Ris, G.F. ; etc.
Kunst der 60er und 70er Jahre aus Bonner Privatbesitz, Kunstmuseum Bonn, 2. November - 5. Dezember 1976
boek
Keywords: Kunstmuseum Bonn